A tool to automatically analyze electromagnetic tracking data from high dose rate brachytherapy of breast cancer patients - Goetz, Th. I.; Lahmer, Godehard; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (PLoS ONE, 2017)
During High Dose Rate Brachytherapy (HDR-BT) the spatial position of the radiation source inside catheters implanted into a female breast is determined via electromagnetic tracking (EMT). Dwell positions and dwell times of the radiation source are established, relative to the patient's anatomy, from an initial X-ray-CT-image. During the irradiation treatment, catheter displacements can occur due to patient movements. The current study develops an automatic analysis tool of EMT data sets recorded with a solenoid sensor to assure concordance of the source movement with the treatment plan. The tool combines machine learning techniques such as multi-dimensional scaling (MDS), ensemble empirical mode decomposition (EEMD), singular spectrum analysis (SSA) and particle filter (PF) to precisely detect and quantify any mismatch between the treatment plan and actual EMT measurements. We demonstrate that movement artifacts as well as technical signal distortions can be removed automatically and reliably, resulting in artifact-free reconstructed signals. This is a prerequisite for a highly accurate determination of any deviations of dwell positions from the treatment plan.
EVALuna2:33034

Cell-to-cell distances between tumor-infiltrating inflammatory cells have the potential to distinguish functionally active from suppressed inflammatory cells - Nagl, Sandra; Haas, M.; Lahmer, Godehard; Buettner-Herold, M.; Grabenbauer, Gerhard; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2016)
Beyond their mere presence, the distribution pattern of inflammatory cells is of special interest. Our hypothesis was that random distribution may be a clear indicator of being non-functional as a consequence of lack of interaction. Here, we have assessed the implication of cell-to-cell distances among inflammatory cells in anal squamous cell carcinoma and a possible association with survival data. Thirty-eight patients suffering from anal carcinoma were studied using tissue microarrays, double staining immunohistochemistry, whole slide scanning and image analysis software. Therapy consisted of concurrent radiochemotherapy. Numbers of stromal and intraepithelial tumor-infiltrating inflammatory cells (TIC) and the distances between cells were quantified. Double-staining of FoxP3(+) cells with either CD8(+), CD1a(+) or CD20(+) cells was performed. Measured cell-to-cell distances were compared to computer simulated cell-to-cell distances leading to the assumption of non-randomly distributed and therefore functional immune cells. Intraepithelial CD1a(+) and CD20(+) cells were randomly distributed and therefore regarded as non-functional. In contrary, stromal CD20(+) cells had a non-random distribution pattern. A non-random distance between CD20(+) and FoxP3(+) cells was associated with a clearly unfavorable outcome. Measured distances between FoxP3(+) cells were distinctly shorter than expected and indicate a functional active state of the regulatory T cells (Treg). Analysis of cell-to-cell distances between TIC has the potential to distinguish between suppressed non-functional and functionally active inflammatory cells. We conclude that in this tumor model most of the CD1a(+) cells are non-functional as are the intraepithelial CD20(+) cells, while stromal CD20(+) cells and FoxP3(+) cells are functional cells.
EVALuna2:18358

Effects of Hippocampal Sparing Radiotherapy on Brain Microstructure—A Diffusion Tensor Imaging Analysis - Dinkel, Johannes; Lahmer, Godehard; Mennecke, Angelika; Hock, Stefan; Richter-Schmidinger, Tanja; Fietkau, Rainer; Distel, Luitpold; Putz, Florian; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2022)
Hippocampal-sparing radiotherapy (HSR) is a promising approach to alleviate cognitive side effects following cranial radiotherapy. Microstructural brain changes after irradiation have been demonstrated using Diffusion Tensor Imaging (DTI). However, evidence is conflicting for certain parameters and anatomic structures. This study examines the effects of radiation on white matter and hippocampal microstructure using DTI and evaluates whether these may be mitigated using HSR. A total of 35 tumor patients undergoing a prospective randomized controlled trial receiving either conventional or HSR underwent DTI before as well as 6, 12, 18, 24, and 30 (±3) months after radiotherapy. Fractional Anisotropy (FA), Mean Diffusivity (MD), Axial Diffusivity (AD), and Radial Diffusivity (RD) were measured in the hippocampus (CA), temporal, and frontal lobe white matter (TL, FL), and corpus callosum (CC). Longitudinal analysis was performed using linear mixed models. Analysis of the entire patient collective demonstrated an overall FACC decrease and RDCC increase compared to baseline in all follow-ups; ADCC decreased after 6 months, and MDCC increased after 12 months (p ≤ 0.001, 0.001, 0.007, 0.018). ADTL decreased after 24 and 30 months (p ≤ 0.004, 0.009). Hippocampal FA increased after 6 and 12 months, driven by a distinct increase in ADCA and MDCA, with RDCA not increasing until 30 months after radiotherapy (p ≤ 0.011, 0.039, 0.005, 0.040, 0.019). Mean radiation dose correlated positively with hippocampal FA (p < 0.001). These findings may indicate complex pathophysiological changes in cerebral microstructures after radiation, insufficiently explained by conventional DTI models. Hippocampal microstructure differed between patients undergoing HSR and conventional cranial radiotherapy after 6 months with a higher ADCA in the HSR subgroup (p ≤ 0.034).
CRIS-Team Scopus Importer:2022-07-22
Keywords: cognitive impairment; cranial radiotherapy; diffusion tensor imaging; fractional anisotropy; hippocampal sparing radiotherapy; hippocampus

On the use of particle filters for electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Lahmer, Godehard; Brandt, Tobias; Kallis, Karoline; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
Modern radiotherapy of female breast cancers often employs high dose rate brachytherapy, where a radioactive source is moved inside catheters, implanted in the female breast, according to a prescribed treatment plan. Source localization relative to the patient's anatomy is determined with solenoid sensors whose spatial positions are measured with an electromagnetic tracking system. Precise sensor dwell position determination is of utmost importance to assure irradiation of the cancerous tissue according to the treatment plan. We present a hybrid data analysis system which combines multi-dimensional scaling with particle filters to precisely determine sensor dwell positions in the catheters during subsequent radiation treatment sessions. Both techniques are complemented with empirical mode decomposition for the removal of superimposed breathing artifacts. We show that the hybrid model robustly and reliably determines the spatial positions of all catheters used during the treatment and precisely determines any deviations of actual sensor dwell positions from the treatment plan. The hybrid system only relies on sensor positions measured with an EMT system and relates them to the spatial positions of the implanted catheters as initially determined with a computed x-ray tomography.
EVALuna2:33033

Prerequisites for the clinical implementation of a markerless SGRT-only workflow for the treatment of breast cancer patients - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Purpose: A markerless workflow for the treatment of breast cancer patients has been introduced and evaluated retrospectively. It includes surface-guided radiation therapy (SGRT)-only positioning for patients with small cone beam CT (CBCT) position corrections during the first five fractions. Prerequisites and the frequency of its clinical application were evaluated, as well as potential benefits in terms of treatment time and dose savings, the frequency of CBCT scans, and the accuracy of the positioning. Methods: A group of 100 patients treated with the new workflow on two Versa HD linacs has been compared to a matched control group of patients treated with the former workflow, which included prepositioning with skin markings and lasers, SGRT and daily CBCT. The comparison was based on the evaluation of logfiles. Results: Of the patients treated with the new workflow, 40% did not receive daily CBCT scans. This resulted in mean time savings of 97 s, 166 s and 239 s per fraction for the new workflow, for patients treated without daily CBCT and for SGRT-only fractions, respectively, when compared to the old workflow. Dose savings amounted to a weighted computed tomography dose index reduction of CTDIW = 2.56 cGy on average for normofractionated treatment and weekly CBCTs, while for patients not treated with daily CBCT, SGRT-based positioning accuracy was 5.2 mm for the mean translational magnitude, as evaluated by CBCT. Conclusion: For 40% of the patients, after five fractions with small CBCT corrections, the workflow could be changed to SGRT-only positioning with weekly CBCT. This leads to imaging dose and time savings and thus also reduced intrafraction motion, potentially increased patient throughput and patient comfort, while assuring appropriate positioning accuracy.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Breast neoplasms; Interfraction motion management; Intrafraction motion management; Markerless radiation therapy; Surface-guided radiation therapy

Recurrent glioblastoma: who receives tumor specific treatment and how often? - Steffens, Rieke; Semrau, Sabine; Lahmer, Godehard; Putz, Florian; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Fietkau, Rainer (Journal of Neuro-Oncology, 2016)
The recurrence of glioblastoma (rGBM) is inevitable and often short-term. Therefore, information on the prognosis and effectiveness of tumor-specific versus purely palliative approaches should be more in-depth than a mere list of available treatment options for patients in this situation. However, follow-up data on the course of the disease in unselected patient populations after completion of primary treatment are scarce. This single-center analysis investigated the rate and number of glioblastoma recurrences after initial radiotherapy in 189 consecutive GM patients, focusing on the incidence of early death and the frequency of tumor-specific treatment (TST) versus best-supportive care (BSC) as well as the outcomes for the different approaches. In 61 % of initial population first recurrence (rGBM) could be determined by histology or imaging. 47 % received TST. 58 % of the patients with rGBM and TST were diagnosed with a second recurrence. Up to five recurrences were treated. 35-45 % of patients died before undergoing imaging studies to confirm the next recurrence. Multivariate analysis identified male sex and KPS score as independent factors (p < 0.01) for the choice of TST over BSC. Median overall survival from the diagnosis of first recurrence was 267 days in the TST group versus 65 days in patients receiving BSC (p < 0.0001). Nearly half of all rGBM patients received second-line TST, but a remarkably high proportion died early. Gender and KPS played a role in the choice of TST over BSC for recurrence treatment.
EVALuna2:18351

Region of interest optimization for radiation therapy of breast cancer - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose: The goal of this study was to investigate how the choice of the region of interest (ROI) affects the registration results of surface imaging for daily positioning of breast cancer patients. Methods: The AlignRT system (VisionRT, London) and the XVI Cone beam CT (CBCT; Elekta, Stockholm) installed on two Versa HD linacs (Elekta) were used in this study, which included 28 patients (160 fractions). In the clinical workflow, patients were prepositioned with AlignRT and then shifted in 6 degrees of freedom (DOF) according to the CBCT. A new reference capture was taken immediately afterward. Retrospectively, the surface capture resulting from prepositioning was registered to the latest reference capture. By varying the ROI used for registration, the surface-based results were optimized in terms of minimizing the deviation to the clinically applied CBCT shifts. Two sets of ROIs were used: one obtained by applying a variable margin to the breast surface, another by combining ROIs of anatomical structures, including the sternum and contralateral breast. Results: Registration results showed significant differences from one ROI to another. Generally, the results improved with increasing ROI size, especially for rotational DOFs. ROIs, including the axilla or supraclavicular lymph drainage region, did not yield an improved registration result. On the other hand, an ROI comprising the breast surface, sternum, and a belt caudal to the breasts decreased the average magnitude of the translational and rotational deviations by 6.6% and 30.8% (p < 0.01), respectively, compared to the breast surface only results. Conclusion: The influence of the ROI choice on surface imaging registration results was analyzed and the surface-based shifts were compared to clinically applied CBCT shifts. An optimal ROI for the treatment of breast cancer patients, consisting of the breast surface, sternum, and a belt, was identified.
CRIS-Team Scopus Importer:2021-10-01
Keywords: breast cancer; radiation therapy; surface guided radiation therapy